The spectrum between substrates and inhibitors: Pinpointing the binding mode of dengue protease ligands with modulated basicity and hydrophobicity - Dražić, Tonko; Kühl, Nikos; Gottscheber, Nicole; Hacker, Christina N.; Klein, Christian D. (Bioorganic & medicinal chemistry, 2021)
Peptides can be inhibitors and substrates of proteases. The present study describes the inhibitor- vs. substrate-like properties of peptidic ligands of dengue protease which were designed to provide insight into their binding modes. Of particular interest was the localization of the cleavable peptide bond and the placement of hydrophobic elements in the binding site. The findings provide clues for the design of covalent inhibitors in which electrophilic functional groups bind to the catalytic serine, and in addition for the development of inhibitors that are less basic than the natural substrate and therefore have an improved pharmacokinetic profile. We observed a tendency of basic elements to favor a substrate-like binding mode, whereas hydrophobic elements decrease or eliminate enzymatic cleavage. This indicates a necessity to include basic elements which closely mimic the natural substrates into covalent inhibitors, posing a challenge from the chemical and pharmacokinetic perspective. However, hydrophobic elements may offer opportunities to develop non-covalent inhibitors with a favorable ADME profile and potentially improved target-binding kinetics.